Using service broker for cloud computing environment - Ebtehal Yahia Abdelbacky Nassar; Ehab E. Hassanien; Sherif A. Mazen (Cairo : Ebtehal Yahia Abdelbacky Nassar, 2016)
The elasticity and the ability to scale up and down has recently become a strongly required feature in the applications design, to meet the rapid change in the cloud environment. As long as tightly coupled components cannot be scaled up or down, there{u2019}s a need to loosen components as much as it can be. One of the main characteristics of the standard applications (like three tier architecture applications) is the strong and tight coupling between applications and databases. This tight coupling means that if the database changes, a ripple effect occurs throughout the interacting applications. Problems also increase during the design phase, as well as the development and maintenance phases. The tight coupling became a strong problem, due to the fact that some applications may need to deal with different database types (relational and NoSQL) at the same time. There were a lot of trials to solve this problem. Some models were developed to solve the tight coupling problem, like ORM (Object Relational Mapping). Other models were proposed to achieve the property of running the same application on relational and NoSQL stores by using universal query languages
Thesis (M.Sc.) - Cairo University - Faculty of Computer and Information - Department of Information Systems
Issued also as CD
Keywords: Cloud computing; Tight and loose coupling; Web services